Adaptation and Integration of Clients of Asylum Houses to Ordinary Life in Relation to Basic Knowledges Resulting from Framework Educational Program for Basic Education - Novakova, Zdenka; Opletalova, Alena; Pitnerova, Dagmar (Civilia, 2020)
The Ministry of Labor and Social Affairs acts at the central level as a ministry managing social policy, social work. In our case, it is work with people in housing need, prevention of loss of housing, social services (dormitories, shelters, halfway houses) and social housing benefits (housing allowance, housing supplement and emergency immediate assistance). The role of partial social aspects in the social housing system is not only supportive, but is absolutely crucial for its functioning. In particular, social work, but also social services, are an essential part of social housing, especially for people in housing need. The priority steps are to solve the problems of eliminating the trade in social exclusion, improving coexistence in the community and not overloading the benefit system. Within the process of adaptation of homeless people in shelters, the key areas are financial literacy, retraining, the possibility of housing mediation and subsequent cooperation of relevant institutions with an emphasis on the integration of these entities into everyday life. However, the persons concerned should already have standard knowledge and skills in connection with the information obtained during compulsory school attendance in the framework of completing primary education in primary schools, where the basic guidelines for the content of the subject matter are set out in the framework curriculum for basic education.
Keywords: Client; Adaptation; Integration; Shelters; Housing; Financial literacy; Retraining; Knowledge; Skills; General educational program